PENGARUH POLA KOMUNIKASI ORANG TUA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK - Lia Istifhama; Elly Nur Aini (Jurnal Keislaman, 2022)
Abstract This study takes the title Of Influence of Parental Communication Patterns On Learning Motivation of Children Grade 2A in Madrasah Ibtidaiyah Tanada school year 2020-2021. The reason for the selection of titles is sensitivity to online learning conditions that place parents as the foundation of absorption of knowledge in their children. So it is expected that the active role of parents in making decisions about their parties, their children, services that are expected to be obtained and that can be provided by their parties and the community. Parents who have the authority in raising students. Parents also have children in the education unit environment and a number of parents from marginal groups most in need outside the target education unit. This research has a formula as well as a goal, which is to know the communication patterns of parents of 2A students at MI Tanada Sidoarjo, the level of learning motivation of the learners, and knowing the influence of parental communication patterns on the motivation of learning learners there. Abstrak Penelitian ini mengambil judul Pengaruh Pola Komunikasi Orang Tua Terhadap Motivasi Belajar Anak Kelas 2A di Madrasah Ibtidaiyah Tanada tahun pelajaran 2020-2021. Alasan pemilihan judul adalah kepekaan terhadap kondisi pembelajaran daring yang menempatkan orang tua sebagai pondasi penyerapan ilmu pada anak-anaknya. Sehingga diharapkan peran aktif orang tua dalam mengambil keputusan tentang pihaknya, anaknya, pelayanan yang diharapkan diperoleh dan yang dapat diberikan oleh pihaknya dan masyarakat. Orang tua yang mempunyai kewenangan dalam membesarkan peserta didik. Orang tua juga mempunyai anak di lingkungan satuan pendidikan dan sejumlah orang tua dari kelompok marjinal paling membutuhkan diluar satuan pendidikan sasaran. Penelitian ini memiliki rumusan sekaligus tujuan, yaitu ingin mengetahui pola komunikasi orang tua peserta didik kelas 2A di MI Tanada Sidoarjo, tingkat motivasi belajar peserta didik tersebut, serta mengetahui pengaruh pola komunikasi orang tua terhadap motivasi belajar peserta didik disana..